Randomized controlled trial comparing efficacy and acceptability of split- and standard-dose sodium picosulfate plus magnesium citrate for bowel cleansing prior to colonoscopy - Manes, Gianpiero; Repici, Alessandro; Hassan, Cesare (Endoscopy, 2014)
Background and study aim: Sodium picosulfate plus magnesium citrate (PMC) is a very effective, safe, and tolerated low-volume preparation for colon cleansing. This study evaluates whether split dosing is associated with a further increase in efficacy and acceptability compared with the standard dosing regimen.Patients and methods: This was a multicenter, randomized, single-blind study. Adult outpatients undergoing colonoscopy received PMC either in the standard dosing (two sachets taken the day before endoscopy) or in split dosing (the second sachet taken on the morning of colonoscopy). Bowel cleansing was assessed using the Boston Bowel Preparation Scale (BBPS) and was rated as adequate when BBPS was ≥ 2 in each segment. Patient acceptance, satisfaction, and related symptoms were recorded. Results: A total of 862 patients were included in the study (577 in the standard group and 285 in the split-dose group). Preparation was adequate in only 69.8 % of patients in the standard group compared with 85.8 % of those in the split-dose group (P = 0.0001). Mean BBPS scores for the whole colon and the right colon were also statistically significantly higher in the split-dose group (P = 0.0001). Both regimens were well tolerated, and only 8.0 % of patients reported discomfort. Compliance was better with the split regimen (0.7 % vs. 7.1 % unable to take 75 % of the preparation; P < 0.0001), and willingness to repeat the preparation was similar. Performing colonoscopy within 6 hours after preparation was associated with better colon cleansing. Other predictors of poor cleansing at multivariate analysis were constipation, obesity, and discomfort during preparation. Conclusions: The split-dose regimen of PMC was superior to the standard regimen in terms of effective colon cleansing and compliance.ClinicalTrial.gov (NCT01909219)